Meeting the Needs of Diverse Students: Enhancing School Counselors’ Experience - Judy R. Hughey (Educational Considerations, 2011)
The National Council for Accreditation of Teacher Education (NCATE) is the premier teacher education program accreditation body. In addition to reviewing teacher preparation programs in institutions of higher learning, NCATE also reviews school administration programs and other school specialist programs, including school counseling programs.
Keywords: Diverse; students; enhancing; school; higher learning; American School Counselor Association (ASCA)